Pelatihan Desain Grafis Untuk Mendukung Kreativitas Murid SMK Negeri 1 - Lilis Anggraini; Muhammad Saidi Rahman; Hoiriyah Hoiriyah (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2022)
At first graphic design began to be known and used by humans because of the need to communicate using visual language from the 19th century to the modern century as it is now. which is a form of communication that is carried out visually that utilizes images, writing, and lines as a medium to become a message so that it can be used as a communication tool directly or indirectly to communicate with others. Design is an illustration that shows complicated geometry, it seems simple and unaesthetic, but to find the initial idea, it is necessary to analyze until the creation of a new design, in which graphic design is a human way of thinking to interpret information presented in a simple form. with the implementation of this training carried out at the Lab of SMKN 1 Banjarmasin and the participants of this activity were students of class X in the Department of Computer Network Engineering with a total of 9 students and in class XI of the Department of Computer Network Engineering a total of 9 students. This implementation is carried out for 3 days with time starting from 08.00 - 16.00. As for the method used in the implementation of this activity by giving material and direct practice using cellphones and laptops, it is known that participants can balance, adjust contrast, and color or give patterns to objects and can design and make logos more attractive and can applied individually or in groups to hone existing ideas and new creativity for their initial provision to enter the world of work